PEMBERDAYAAN UMKM MELALUI LITERASI TRANSAKSI DIGITAL, AFFILIATE MARKETING, DAN PENGELOLAAN PELANGGAN - Sadana Devica; Mentari Septynaputri Widodo; Reina A Hadikusumo (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt to digital transformation in order to enhance competitiveness and business sustainability. However, many MSMEs still face challenges in adopting digital transactions, digital marketing strategies, and customer relationship management. This community service activity aims to improve MSMEs’ literacy and skills in digital transactions (mobile banking and QRIS), affiliate marketing strategies, and customer relationship management. The training involved 27 MSME actors in Surabaya, covering various business sectors such as food, beverages, fashion, and accessories crafts. The methods included preparation, implementation, and interactive training sessions delivered by three lecturers from the Marketing Management Study Program, Politeknik UBAYA. The training materials covered digital payment systems, affiliate marketing implementation using e-commerce platforms, and strategies for managing customer relationships effectively. The results showed high participant enthusiasm, increased understanding of QRIS implementation, successful creation of affiliate accounts, and improved awareness of customer engagement strategies. Overall, the program contributed positively to enhancing MSME digital literacy and practical skills. However, continuous assistance is still required to ensure sustainable implementation of digital strategies in business development.